2001
DOI: 10.1037/0735-7028.32.5.507
|View full text |Cite
|
Sign up to set email alerts
|

Can positive emotion influence problem-solving attitudes among suicidal adults?

Abstract: A client's mood can hinder or enhance treatment and its effectiveness. Positive emotions can encourage exploration and experimentation, and they may have the long-term effect of resource building. The purpose of the present study was to assess this perspective as applied to the treatment of suicidal individuals. The authors found that patients prone to positive moods, as compared with those less prone to such moods, displayed more positive problem-solving attitudes following treatment for suicidal symptoms, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 32 publications
1
39
1
3
Order By: Relevance
“…Clinicians who induce positive emotions (e.g., by asking patients to think about their "best times") or who time skill-based interventions to correspond to patients' naturally-occurring positive moods may increase the chances that patients will more rapidly and fully learn therapy-based skills (Wingate et al, 2006). Previous research has empirically substantiated the beneficial impact of positive emotional experiences on treatment outcome, even among suicidal patients (Joiner et al, 2001). More generally, evidence for upward spiral relations suggests that people's experiences of positive emotions-although fleeting-may carry largely unsung value.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians who induce positive emotions (e.g., by asking patients to think about their "best times") or who time skill-based interventions to correspond to patients' naturally-occurring positive moods may increase the chances that patients will more rapidly and fully learn therapy-based skills (Wingate et al, 2006). Previous research has empirically substantiated the beneficial impact of positive emotional experiences on treatment outcome, even among suicidal patients (Joiner et al, 2001). More generally, evidence for upward spiral relations suggests that people's experiences of positive emotions-although fleeting-may carry largely unsung value.…”
Section: Discussionmentioning
confidence: 99%
“…At the core of his recent thinking is the concept of the 'primal mode', which is a more basic, and more physical, emotional and motivational, form of information processing than the schema. Researchers found that suicidal patients displayed better problem-solving skills and attitudes in treatment when in positive moods, showing that emotion and cognition can interact in diverse ways (Joiner et al, 2001). Wells and Carter (2001) found support for a cognitive model of Generalized Anxiety Disorder that is characterized by 'Type 2' worry, that is perseverative worry about the harmful consequences of one's already frequent worrying.…”
Section: Emotional Processing and Exposure Therapymentioning
confidence: 97%
“…Positive emotions in suicidal patients have been linked to improved problem-solving [17], and a study of patients hospitalized for self-harm found that low positive future orientation more strongly predicted recurrent selfharm after discharge than did global hopelessness [18]. Therefore, explicit targeting of positive cognitive and emotional states like gratitude and positive future orientation may have effects on suicide risk above and beyond standard approaches.…”
Section: Introductionmentioning
confidence: 99%